A case study describing factors perceived to be impacting staff satisfaction amongst health care professionals at the East London Hospital complex - Galo, Luntu (Rhodes University, Faculty of Commerce, Rhodes Business School, 2012)
This thesis was born from a concern the researcher had with regard to negative reports in the media emanating from 4 babies that died at Cecilia Makiwane Hospital Peadiatric ICU unit due to power supply failure. The most significant of these negative reports was in 2007 when the Daily Dispatch ran a series of articles regarding what they termed avoidable deaths over the last 14 years. The ease with which staff communicated with the media together with the high absenteeism rate and high turnover was a cause for concern. When the researcher analysed the history of the problem, it immerged from the respondents' responses that the rationalistion process undertaken by the Eastern Cape Department of Health (ECDoH) was a significant root cause to the problem. The literature review focused on three areas viz.: Organisational Culture, Organisational Change, Foundations of Satisfaction. This focus was used to confine the problem to a manageable project but secondly each of the aspects are interwoven. Routledge (2010) notes that culture is the reflection of the values advocated by a founder or leader by way of his/her day to day actions. This is done by the leader creating a perception or viewpoint that assists the employees to achieve the organisation's mission, vision and goals. In any organisation change is a constant and it needs to be effectively managed. With government institutions like the East London Hospital Complex (ELHC) directives come from the top and are implemented by an unprepared and untrained leadership and management cadre and clear communication of vision and objective of the desired outcomes never happens. The aim of the research was to: describe the existing Organisational Culture present at ELHC (Perform an organisational diagnosis); describe the impact of change (rationalisation) and to analyze why there was such a high staff turnover. It is clear from the results of the survey conducted that significant dissatisfaction prevailed relating to how the institution was managed. Dissatisfaction amongst the health professionals was general but also specific to the following: leadership and management issues, fairness, remuneration and lack of resources. The recommendations therefore focused on developing management and leadership within the proposal of Dubrin's model (2001).
Keywords: Medical personnel -- Job satisfaction -- South Africa -- Case studies; Medical personnel -- Job stress -- South Africa -- Case studies; Medical personnel -- South Africa -- Attitudes -- Case studies; Hospitals -- South Africa -- Administration; Health services administration -- South Africa; Health planning -- South Africa